Reply to 'Some More Comments on Folate Deficiency in Chronic Pancreatitis' - Braganza, Joan M (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Space filling model of folic acid from drugbank.ca data (Author: Lanulos; Wikimedia Commons).